Formulation, Optimization, and Characterization of Curcumin-Loaded Nanoemulsion using Glyceryl Monostearate and Croduret 40 (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
An ultrasonication approach was employed to synthesize a Curcumin Nanoemulsion (CUNL), aiming to optimize the encapsulation and stability of curcumin nanoparticles. The synthesis process was guided by Design Expert software, which recommended the utilization of glycerol monostearate (GMS) at a concentration of 0.57 mg/ml and Croduret 40 at 0.25% as key emulsifying agents. This optimization resulted in the formation of nanoparticles with an average size of 187 nm and an encapsulation efficiency of 65.9%, indicating effective entrapment of curcumin within the nanoemulsion matrix.Characterization of the synthesized CUNL revealed a zeta potential value of -25.4 mV, which is indicative of the nanoemulsion's stability due to sufficient electrostatic repulsion between particles, preventing aggregation. The polydispersity index (PDI) was calculated to be 0.55, reflecting a moderate degree of heterogeneity within the nanoparticle population. Furthermore, the viscosity of the nanoemulsion was measured at 10.87 mPa·s, and the pH was determined to be 6.03, both parameters consistent with the desired characteristics for potential biomedical applications.